Anatomical preparation of the visceral aspect of the human liver to demonstrate the branches of the hepatic portal vein applying the Laskowski filling, dissection and conservation techniques: Anatomical preparation of the visceral aspect of the human liver to demonstrate the branches of the hepatic portal vein - Balarezo Rebaza, Emanuel Sebastian (2024)
The Human Anatomy course is crucial in the education of medical students, and therefore, the shortage of anatomical specimens poses a challenge in teaching. This study aims to create an anatomical preparation of the visceral surface of the liver, allowing visualization of the branches of the hepatic portal vein using the repletion, dissection, and Laskowski preservation techniques. The preparation successfully revealed the distribution of suprahepatic veins and branches of the portal vein irrigating their respective segments, without encountering anatomical variations. The study successfully produced an anatomical specimen primarily showcasing the branches of the hepatic portal vein. We recommend inspecting